The comparison of performance and injury incidence rate in home and away games in Iran Premier League teams - Rahnama, N.; Bambaeichi, E.; Zarei, M. (World Journal of Sport Sciences, 2009)
In soccer, home advantage is a very important factor in determining the outcome of a game. The main purpose of this study was to compare the performance and injury incidence rate in home and away games in Iran Premier League. The information about the number of wins, lost, received goals, scored goals, yellow and red cards in home and away teams were obtained via the website of www.iplstats.com. Then, videotapes for 253 matches of this league were selected and analyzed. The results showed that when teams played at home, they scored significantly higher points than when they played away (p<0.05, t = 4.2). The number of wins in home games was significantly higher than the away games (p<0.05, t = 3.8). The number of lost in away games was higher than home games (p<0.05, t =-4.6). Injury rate for away teams was significantly higher than home teams (Z = 1.98, P<0.05) (57.6 injuries per 1000 hours vs. 72.01 injuries per 1000 hours). Consequently, the results showed more ideal performance of the teams in home games. The rate of injury in away teams was significantly higher than home teams. Thus, these factors must be considered by team coaches and physicians to prevent injuries and to enhance performance.